UNIFFERENTIATED CONNECTIVE TISSUE DYSPLASIA AS A POTENTIAL PREDICTOR OF ARTERIAL HYPERTENSION DEVELOPMENT IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Sherstyuk, Ludmila; Nikolenko, Yevgen (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2019)
The article presents the results of studies of markers of connective tissue dysplasia and the content of the main fibroblast growth factor in blood plasma in patients with type 2 diabetes. The presence of significant correlations between the studied parameters with the occurrence and progression of hypertension in patients with type 2 diabetes is established. A regression model for predicting the development of arterial hypertension is proposed in patients with diabetes mellitus.The development of hypertension in patients with DM type 2 in combination with UCTD occurs earlier, is almost independent of the duration of diabetes, more pronounced hypertension is observed in patients with visceral and skeletal symptoms of UCTD. This is evidence of the role of UCTD in the pathogenesis of hypertension in patients with type 2 diabetes.Essential role in the emergence and progression of hypertension in patients with DM type 2 is played by metabolic disorders of the connective tissue that manifests as clinical signs of UCTD. FGF2, which content is increased in patients with visceral and/or skeletal symptoms of UCTD, is involved in its pathogenesis.The regression model of the prediction of hypertension in patients with DM type 2 with an assessment of the presence of UCTD signs and the duration of diabetes has a high prognosticity, specificity and sensitivity, which makes it possible to apply this method in clinical practice to determine patients with high risk of development of hypertension.